2021
DOI: 10.3390/cancers13123091
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Infusion of Chemotherapy for Advanced Hepatobiliary Cancers: State of the Art

Abstract: Liver functional failure is one of the leading causes of cancer-related death. Primary liver tumors grow up mainly in the liver, and thus happens for liver metastases deriving from other organs having a lower burden of disease at the primary site. Systemic chemotherapy usually offers a modest benefit in terms of disease control rate, progression-free survival, and overall survival at the cost of a significant percentage of adverse events. Liver malignancies are mostly perfused by the hepatic artery while the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 98 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…The liver's collateral blood flow allows for the blockage of abnormal lobar arteries and the following crossover perfusion by vessels which are nonligated. In the case of abnormal HA architecture, this makes catheter placement easier [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The liver's collateral blood flow allows for the blockage of abnormal lobar arteries and the following crossover perfusion by vessels which are nonligated. In the case of abnormal HA architecture, this makes catheter placement easier [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the infusion of an initial bolus allows the therapeutic window to be reached more rapidly, which is then sustained by the subsequent c.i. Literature data have already evaluated the 5-FU liver extraction rate after HAI, which is approximately 75–80% [ 24 ], and several clinical trials have demonstrated remarkable efficacy in the treatment of primary and secondary hepatic malignancies. Tao et al tested the pharmacokinetic differences between PAI and the intravenous infusion of 5-FU in a Wistar rat model.…”
Section: Pancreatic Arterial Infusion Of Chemotherapymentioning
confidence: 99%
“…In summary, the poor prognosis, the limited treatment strategies, and the anatomical and biological features of PC justify the medical need for new therapeutic options. One recent promising route is the application of loco-regional therapies, particularly the pancreatic arterial infusion (PAI) of chemotherapy, delivering remarkably higher concentrations of antineoplastic agents to the tumor site than systemic administration and limiting adverse events (AEs).This type of therapeutic approach has already been successfully evaluated in various solid tumors, specifically in primary and metastatic liver cancers [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. As for advanced PC, only a few clinical trials have investigated the safety and efficacy of PAI with promising results, especially in terms of high response rates (RRs) compared to systemic chemotherapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a general point of view, the main clinical studies of IA infusion chemotherapy have been performed for liver metastases from colorectal and breast cancers, and primary hepatobiliary tumors ( 14 , 25 , 26 ). These clinical reports have indicated that IA infusion chemotherapy is safe and can provide very encouraging results.…”
Section: Discussionmentioning
confidence: 99%